Aplikasi Kajian DNA Molekuler dan Fenotipik Pada Program Pelepasliaran Burung Kakatua - Zein, Moch Syamsul Arifin; Haryoko, Tri; Fitriana, Yuli Sulistya; Sulistyadi, Eko; Prawiradilaga, Dewi Malia (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThere are six species of cockatoos in Indonesia which are well known as exotic, smart, and they can be trained in a variety of attractions. Thus, many people want to keep those birds as pets. All of pets which have been kept by community should be evaluated from various aspects before being reintroduced to their natural habitat. The examination of sex and species of illegal cocktoos play as a key role for the reintroduction programme. Theobjective of this study was to evaluate the reliability and effectivity of evaluation technique of morphometric and molecular for reintroduction programme of cockatoos. We used the COI gene sequences from 68individuals of cockatoos from pet communities in and around Jakarta and four sequences from GenBank. The phylogenetic analysis used the neighbor-joining method, in which the genetic distance matrix calculations with Kimura 2-parameter models that are implemented on a pairwise distance calculation in the MEGA program version 6:05. The result of the genetic variation of the cockatoo species which shows intraspecific divergence was Cacatua alba (n=4)= 0%, C. galerita (Australia n=9)= 0.6%, C. galerita (Indonesia n=53)= 0.3%, C .goffiniana (n=3)= 0%, C. moluccensis (n=7)= 0.1%, and C. sulphurea (n=2)= 0.3%, with a range of 0-0.6%. The results indicate that the average of intraspecific of COI in the cockatoos community was 0.25±0.055%, and interspecific divergences ranged from 3.1 to 11.6%. The phylogenetic tree shows the monophyletic clade of cockatoo species in Indonesia. In addition, DNA barcode analysis and molecular sexing could correct the error and doubts the result of five individual species identification and two individual sexing identification of C.galerita by morphological identification. The results of morphological examanation base on body weight, body length and head-bill length of C. galerita triton were not significantly different (P?0,5). Finally, 19 individuals C. galerita triton and two individuals P. aterrimus were reintroduced to their natural habitat.Keywords: cockatoo, barcodes DNA, reintroduction